?TETRA CYCLIC HETEROAROMATIC SYSTEMS. PART-II. BENZIMIDAZO [1, 2-a] BENZIMIDAZOLES (Biological Sciences - PJSIR, 2000)
Benzimidazo [1. 2-a 1benzimadozoles (1, R=H) were synthesized by the trialkylphosphite-induced deoxygenation and thermolysis of l-o-nitrophenyl and l-o-azidophenyl benzimidazole. Spectral and other properties of the product and the intermediate compounds are reported.